Advertising Effects? An Elemental Experiment. Issue 4 (November 2018) - Pochun, Tej; Brennan, Linda; Parker, Lukas
This paper examines the effects of the textual (headline, body copy and typography) and visual (image) elements of print advertising on the emotional responses of an audience. Six web-based experiments were carried out to determine the causal relationships between elements of print advertisements and viewers' emotional responses. Data were collected from 105 respondents and Crisp Set Qualitative Comparative Analysis (csQCA) was undertaken. Results indicate that viewers were emotionally affected by the textual and visual elements of the advertisements. Moreover, the emotional responses were multivalent, indicating that people experience emotional ambiguity while viewing ads.